Self-Support and Loneliness Among Chinese Primary School Students: A Moderated Mediation Model - Yao, Zhendong; Pang, Lu; Yu, Huiying; Xiao, Hanshi; Peng, Biao (Frontiers in Psychology, 2022)
This study examined the effect of self-support on loneliness, the mediation effect of school belonging, and the moderation effect of self-esteem using a sample comprising 1,126 Chinese mainland primary school students, 621 are boys and 505 are girls, and their mean age was 10.51 years (SD = 1.63, range 8–13). Participants completed questionnaires regarding self-support, loneliness, school belonging and self-esteem. In the model hypothesis, self-support is an independent variable, loneliness is an outcome variable, school belonging is a mediating variable, and self-esteem is a regulatory variable. After controlling the demographic variables, the data were analyzed, and the results showed that: (1) self-support had a significantly negative predictive effect on loneliness; (2) the relation between self-support and loneliness was mediated by school belonging; and (3) the relation between school belonging and loneliness was moderated by self-esteem, supporting the moderated mediation model. Moderated mediation analysis further indicated that the mediated path make loneliness weaker for pupils with higher levels of self-esteem. These results revealed the formation mechanism of loneliness in primary school students and have certain enlightenment significance for the intervention of loneliness in primary school students. These results revealed the formation mechanism of loneliness among primary school students and have significant implications for interventions against loneliness in the primary school context.